The Effect Of Widyaiswara Functional Position Formation On Motivation, Work Discipline, And Performance Of Widyaiswara Functional Officials At Medan Religious Training Center - Yusri Thamrin; Kiki Farida Ferine (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Human resources play a very important role in determining the progress of a country. Even though the country has abundant natural resources, if they are not supported or supported by quality human resources, the country will not be able to progress. The type of research used was associative quantitative. This research was carried out at the Medan Religious Education and Training Center office, the research population was 31 employees and the sampling technique used was a saturated sampling technique because it counted the entire population as a sample, the data collection used was distributing questionnaires, research models This is an analysis process with measuring tools using Smart PLS version 3.3.3. The results of this research are as follows: Formation has a negative and insignificant effect on the Widyaiswara Discipline of the Medan Religious Education and Training Center. Formation has a positive and significant effect on the performance of the Medan Religious Education and Training Center Widyaiswara. Formation has a positive and significant effect on the motivation of the Medan Religious Education and Training Center Widyaiswara.